Demonstrating Successful Aging Using the International - Kathryn A. Atchison, DDS, MPH; Ronald M. Andersen, PhD (Blackwell Synergy, 2000)
As the lifespan increases andpeople are faced with 15 to 20 years of ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œold age,ÃƒÂ¢Ã¢â€šÂ¬Ã‚Â we ask what one considers successful aging with respect to oral health. We propose a comprehensive combination of outcome variables, maintenance of teeth, manageable periodontal condition, positive perceived oral health, satisfaction with their access to and receipt of dental services, and minimal functional problems, that together comprise a definition of successful aging. The International Collaborative Study for Oral Health Outcomes provides a data set for exploring the oral health of a diverse sample of older adults in US and international sites using the modified Andersen Behavioral Model.